Cutaneous manifestations in relation to immunologic parameters in a cohort of primary myelodysplastic syndrome patients. - Dalamaga, M; Karmaniolas, K; Matekovits, A; Migdalis, I; Papadavid, E (J Eur Acad Dermatol Venereol, 2008)
BACKGROUND: Cutaneous lesions in myelodysplastic syndrome (MDS) may be specific or not and may reveal bone marrow transformation. Our purpose was to investigate in a cohort of 84 MDS patients the correlation of cutaneous findings with immunologic parameters and prognostic features of MDS in order to clarify their potential clinical significance. MATERIALS AND METHODS: We studied a cohort of 84 newly diagnosed MDS patients in order to assess the cutaneous findings present at the time of diagnosis and during 1 to 3 years of follow-up. We described the clinical variety of cutaneous findings ascertained by histology. We also looked for any association between the group of MDS patients with skin manifestations and MDS subtype, immunologic and prognostic features highlighting transformation to acute leukaemia. RESULTS: Twenty-one patients presented cutaneous manifestations: 1 patient developed leukaemia cutis, 6 patients photosensitivity not associated with autoimmune disease, 3 prurigo nodularis, 2 Sweet's syndrome, 6 leucocytoclastic vasculitis, 2 ecchymoses and purpura associated with preexisting relapsing polychondritis, 1 patient subcutaneous nodules associated with Wegener's granulomatosis and 1 patient with malar rash and oral ulcers associated with preexisting systemic lupus erythematosus. Adjusted for age and gender, the presence of skin findings constitutes a significant predictor of the high-risk MDS subgroup (odds ratio, 3.59; 95% confidence interval, 1.18-10.92). Hypergammaglobulinemia was significantly higher in the MDS subgroup with skin manifestations (P = 0.03). CONCLUSION: Most MDS patients with cutaneous manifestations belong to the high-risk MDS subgroup and present hypergammaglobulinemia. Early biopsy of skin lesions in myelodysplasia is indicated.
Keywords: Adult; Aged; Aged, 80 and over; Biopsy; Cohort Studies; Disease Progression; Female; Follow-Up Studies; Humans; Hypergammaglobulinemia; Male; Middle Aged; Myelodysplastic Syndromes; Predictive Value of Tests; Prognosis; Risk Factors; skin; Skin Diseases